F12 PA PA PA and PATI PATI PATI – do HD mutation carriers have an evolutionary advantage?. (13th September 2016) - Saft, Carsten; Grönheit, Wenke; Lukas, Carsten; Bellenberg, Barbara; Hein, Sarah von; Hoffmann, Rainer; Skodda, Sabine
Abstract : Background: So far, most research shows a functional decline accompanied by a progredient brain atrophy starting already in the premanifest stage of Huntington's disease (preHD). Speech parameters in manifest HD shows a typical pattern with reduced articulation rates and an increased variability. Very few, however, is known about the pattern of these abnormal features in preHD. Aims: Using an easy to perform speech test we aimed to analyse different speech parameters in preHD. Methods/techniques: 28 preHD mutation carriers and matched healthy controls had to perform a reading task and several syllable repetition tasks. Results of computerised acoustic analysis of different variables for the measurement of speech rate and regularity were correlated with clinical measures and MRI-based brain atrophy assessment by voxel based morphometry. Results/outcome: As already published, 1 crosssectional data showed an increased speech rate compared to controls and showed correlations to the volume of certain brain areas known to be involved in the sensory-motor speech networks. Moreover, speech rate showed correlations to different progression and clinical measures. In addition a higher variation in steadily repeat single syllables was found in preHD compared to healthy controls. In an additional, unpublished 22 month follow-up investigation (n = 13, no phenoconversion) we saw a tendency to a reduction of speech rate and maximal syllable repetition rate, a further decline of the steadiness of syllable repetition (n.s.), the self-chosen pace of syllable repetition was slower and the pa ti-ratio showed irregularities in syllable repetition at follow-up (p < 0.0001 (d = 2.45); p = 0, 005 (d = 1.02) respectively), no changes for tapping and pegboard performance were observed. Conclusions: As one of the possible causes for higher performance in preHD far from onset we discuss huntingtin dependent temporarily evolutionary advantageous development processes of the brain. Measurement of speech rate and regularity might be an easy to perform, cheap and highly sensitive additional tool for the monitoring the course of preHD. Reference: Two different phenomena in basic motor speech performance in premanifest Huntington's disease. Skodda et al., Neurology in press